Marwān ibn Janāḥ: on the nomenclature of medicinal drugs (Kitāb al-talkhīṣ) : edition, translation and commentary, with special reference to the Ibero-Romance terminology - Ibn Janāḥ, Abū al-Walīd Marwān, approximately 990-approximately 1050 (Islamic history and civilization, 2020)
"In early eleventh century Zaragoza, the eminent Jewish scholar Abū l-Walīd Marwān ibn Ǧanāḥ wrote a glossary containing almost 1100 entries, entitled Kitāb al-Talḫīṣ. This important text, considered lost until recently, contains Arabic and foreign-language names of simple drugs, weights, measures, and other medical terms. In the present volume, the Kitāb al-Talḫīṣ is edited and translated for the first time by Gerrit Bos and Fabian Käs. In detailed commentaries, the editors identify the substances mentioned in the Talḫīṣ. They also elaborate on the role of the text in the history of Arabic glossaries concerned with medical nomenclature. Special attention goes out to Ibn Ǧanāḥ's Ibero-Romance phytonyms, analysed in depth by Mailyn Lübke and Guido Mensching"--